Evidence-Base Update for Parenting Stress Measures in Clinical Samples. Issue 5 (3rd September 2019) - Holly, Lindsay E.; Fenley, Alicia R.; Kritikos, Tessa K.; Merson, Rachel A.; Abidin, Richard R.; Langer, David A.
Abstract : Parenting stress is relevant to the development, maintenance, and amelioration of youth mental, emotional, and behavioral health issues. This Evidence Base Update evaluates the empirical literature on the measurement of parenting stress to guide future research and inform clinical decision-making. After a comprehensive literature search, we identified eight well-studied measures of parenting stress, to which we applied the criteria put forth by Hunsley and Mash (2008) and extended by Youngstrom et al. (2017) to evaluate the evidence base for norms, validity, and utility. All measures were rated adequate, good, excellent, or no evidence on 11 psychometric categories (e.g., internal consistency, treatment sensitivity). Overall, the ability of identified measures to accurately and reliably assess parenting stress was strong. Although the psychometrics vary across measures, the aggregated findings support the existence of a parenting stress construct and further confirm the relevance of parenting stress to family functioning, youth psychopathology, and mental health interventions.